High ploidy diversity and distinct patterns of cytotype distribution in a widespread species of Oxalis in the Greater Cape Floristic Region - Krejcíková, Jana; Sudová, Radka; Lucanová, Magdalena; Trávnícek, Pavel; Urfus, Tomás; Vít, Petr; Weiss-Schneeweiss, Hanna; Kolano, Bozena; Oberlander, Kenneth; Dreyer, Leanne L; Suda, Jan (Annals of botany, 2013)
BACKGROUND AND AIMS: Genome duplication is widely acknowledged as a major force in the evolution of angiosperms, although the incidence of polyploidy in different floras may differ dramatically. The Greater Cape Floristic Region of southern Africa is one of the world's biodiversity hotspots and is considered depauperate in polyploids. To test this assumption, ploidy variation was assessed in a widespread member of the largest geophytic genus in the Cape flora: Oxalis obtusa. METHODS: DNA flow cytometry complemented by confirmatory chromosome counts was used to determine ploidy levels in 355 populations of O. obtusa (1014 individuals) across its entire distribution range. Ecological differentiation among cytotypes was tested by comparing sets of vegetation and climatic variables extracted for each locality. KEY RESULTS: Three majority (2x, 4x, 6x) and three minority (3x, 5x, 8x) cytotypes were detected in situ, in addition to a heptaploid individual originating from a botanical garden. While single-cytotype populations predominate, 12 mixed-ploidy populations were also found. The overall pattern of ploidy level distribution is quite complex, but some ecological segregation was observed. Hexaploids are the most common cytotype and prevail in the Fynbos biome. In contrast, tetraploids dominate in the Succulent Karoo biome. Precipitation parameters were identified as the most important climatic variables associated with cytotype distribution. CONCLUSIONS: Although it would be premature to make generalizations regarding the role of genome duplication in the genesis of hyperdiversity of the Cape flora, the substantial and unexpected ploidy diversity in Oxalis obtusa is unparalleled in comparison with any other cytologically known native Cape plant species. The results suggest that ploidy variation in the Greater Cape Floristic Region may be much greater than currently assumed, which, given the documented role of polyploidy in speciation, has direct implications for radiation hypotheses in this biodiversity hotspot.
Keywords: jižní Afrika; Genetic Variation; Ploidies; biodiverzita; Chromosomes, Plant; Genetics, Population; Magnoliopsida; Africa, Southern; Flow Cytometry; genetická variace; ploidie; průtoková cytometrie; chromozomy rostlin; populační genetika; Biodiversity